Mitigating customers' negative responses to physical presence reduction. (July 2017) - Tojib, Dewi; Khajehzadeh, Saman
Abstract: Building on the social exchange theory and presumption of a firm's multi-channel strategy as a customer relationship management initiative, three experimental studies show that: (1) reducing physical presence negatively affects customers' perceived relationship investment and trust and increases their switching intention; (2) to mitigate these negative effects, firms should engage in strategic decisions that benefit customers and are perceived as highly strategic. This research offers new insights suggesting that customers' appraisals of firms' strategic decisions influence their switching intention through the sequential operations of perceived relationship investment and trust. These findings are consistent for both services and retail contexts, highlighting the importance of firms engaging in strategies that are deemed to be unfavorable in the eyes of their customers to be perceived as highly committed to maintaining relationships with their customers.